Prevalence and related factors of inappropriate gestational weight gain among pregnant women with overweight/ obesity in Thailand - Thanyawalai Chairat; Ameporn Ratinthorn; Piyanun Limruangrong; Dittakarn Boriboonhirunsarn (BMC, 2023)
Abstract Background An inappropriate gestational weight gain (GWG) among pregnant women with overweight/obesity is a crucial health problem. Its prevalence remains high worldwide, particularly in urban areas. The prevalence and predicting factors in Thailand are lack of evidence. This study aimed to investigate prevalence rates, antenatal care (ANC) service arrangement, predictive factors, and impacts of inappropriate GWG among pregnant women with overweight/obesity in Bangkok and its surrounding metropolitan area. Methods This cross-sectional, retrospective study used four sets of questionnaires investigating 685 pregnant women with overweight/obesity and 51 nurse-midwives (NMs) from July to December 2019 in ten tertiary hospitals. Multinomial logistic regression identified predictive factors with a 95% confidence interval (CI). Result The prevalence rates of excessive and inadequate GWG were 62.34% and 12.99%. Weight management for pregnant women with overweight/obesity are unavailable in tertiary cares. Over three-fourths of NMs have never received weight management training for this particular group. ANC service factors, i.e., GWG counseling by ANC providers, quality of general ANC service at an excellent and good level, NMs' positive attitudes toward GWG control, significantly decreased the adjusted odds ratio (AOR) of inadequate GWG by 0.03, 0.01, 0.02, 0.20, times, respectively. While maternal factors, sufficient income, and easy access to low-fat foods reduce AOR of inadequate GWG by 0.49, and 0.31 times. In contrast, adequate maternal GWG knowledge statistically increased the AOR of inadequate GWG 1.81 times. Meanwhile, easy access to low-fat foods and internal weight locus of control (WLOC) decreased the AOR of excessive GWG by 0.29 and 0.57 times. Finally, excessive GWG significantly increased the risk of primary C/S, fetal LGA, and macrosomia 1.65, 1.60, and 5.84 times, respectively, while inadequate GWG was not associated with adverse outcomes. Conclusion Prevalence rates of inappropriate GWG, especially excessive GWG remained high and affected adverse outcomes. The quality of ANC service provision and appropriate GWG counseling from ANC providers are significant health service factors. Thus, NMs should receive gestational weight counseling and management training to improve women's knowledge and practice for gestational weight (GW) control.